Credit Risk and Capital as Moderation of Liquidity on Bank Profitability - G. Oka Warmana; I Wayan Suarjana (UNHI Press, 2024)
Purpose – The aim of the research is to investigate how liquidity affects bank profitability in conditions where there is a trade-off between liquidity and bank profitability. Credit risk and capital are related to bank liquidity. The higher the credit risk, the bank needs to provide reserve funds. When liquidity decreases, it can be increased with additional capital Methodology – This research looked at 45 commercial banks operating in Indonesia in the 2017-2022 period. Interaction term is measured by the absolute difference of variables. Findings – The test results show that there is a trade-off between liquidity and profitability, especially in banks with high capital. Originality – This research uses credit risk and bank capital as moderating variables in the case of banking in Indonesia.